Energy Security through Nuclear Energy in India - CHANDRA, SUBHASH; SRIVASTAVA, ARUN; GROVER, R.B. (SCHOOL SCIENCE, 2007)
Indian Economy has shown impressive growth in the recent past and it is expected that it will continue to do so for several decades to come. Growth in economy has to be accompanied by growth of primary energy and electricity consumption. Assuming i) India’s Gross Domestic Product (GDP) growth rate remaining around 5 to 6 % for fifty years to come1 and ii) applicable correlations between GDP growth rate and energy growth rate2, as the GDP multiplies by nearly 15 times in the forthcoming fifty years, primary energy and electricity consumption would also go up.